Modulator property of the intrinsic cortical projection from layer 6 to layer 4 - Lee, Charles C.; Sherman, S. M. (Frontiers in Systems Neuroscience, 2009)
Layer 4 of the sensory neocortex receives widespread convergent inputs from thalamic, intracortical, and corticocortical sources. Yet, the relative information bearing roles for most of these pathways remain largely undefined. Here we show that the intracortical projections from layer 6 to layer 4 exhibit a physiological property that is consistent with a modulator role. Using in vitro slice preparations of the auditory and somatosensory cortices, we found that electrical stimulation or photostimulation of layer 6 elicits a prolonged depolarizing response that is attributable to the activation of group 1 metabotropic glutamate receptors (mGluRs). These results complement the known physiological properties of the layer 6 to layer 4 pathway, and further suggest that this pathway is not a principle conduit for information flow, but rather acts as a modulator of cortical activity.